APPLICATION OF CONSTRUCTIVISM THEORY IN THE LEARNING PROCESS IN SCHOOLS - adeliaridautami adelia (Teaching and General Education Studies, 2026)
The constructivism theory is a learning approach that emphasizes that knowledge is actively constructed by students through experience and interaction in the learning process. In school learning, the application of constructivism is important because it can encourage students to be more active in understanding the material and developing their thinking skills. This article aims to examine the application of constructivism theory in the learning process in schools. The method used is a literature review by examining various sources such as relevant books and scientific journals. The results of the study show that the application of constructivism can be carried out through discussion activities, problem-solving, and learning that involves students' direct experiences. Through this approach, students become more active in building knowledge, while the teacher acts as a facilitator in the learning process. Thus, the application of constructivism theory can create more active and meaningful learning for students.